Intracranial Sonodynamic Therapy With 5-Aminolevulinic Acid and Sodium Fluorescein: Safety Study in a Porcine Model - Raspagliesi, Luca; D’Ammando, Antonio; Gionso, Matteo; Sheybani, Natasha D.; Lopes, Maria-Beatriz; Moore, David; Allen, Steven; Gatesman, Jeremy; Porto, Edoardo; Timbie, Kelsie; Franzini, Andrea; Di Meco, Francesco; et al. (Frontiers in Oncology, 2021)
Background Sonodynamic therapy (SDT) is an emerging ultrasound-based treatment modality for malignant gliomas which combines ultrasound with sonosensitizers to produce a localized cytotoxic and modulatory effect. Tumor-specificity of the treatment is achieved by the selective extravasation and accumulation of sonosensitizers in the tumor-bearing regions. The aim of this study is to demonstrate the safety of low-intensity ultrasonic irradiation of healthy brain tissue after the administration of FDA-approved sonosensitizers used for SDT in experimental studies in an in vivo large animal model. Methods In vivo safety of fluorescein (Na-Fl)- and 5 aminolevulinic acid (5-ALA)-mediated low-intensity ultrasound irradiation of healthy brain parenchyma was assessed in two sets of four healthy swine brains, using the magnetic resonance imaging (MRI)-guided Insightec ExAblate 4000 220 kHz system. After administration of the sonosensitizers, a wide fronto-parietal craniotomy was performed in pig skulls to allow transmission of ultrasonic beams. Sonication was performed on different spots within the thalamus and periventricular white matter with continuous thermal monitoring. Sonication-related effects were investigated with MRI and histological analysis. Results Post-treatment MRI images acquired within one hour following the last sonication, on day one, and day seven did not visualize any sign of brain damage. On histopathology, no signs of necrosis or apoptosis attributable to the ultrasonic treatments were shown in target areas. Conclusions The results of the present study suggest that either Na-FL or 5-ALA-mediated sonodynamic therapies under MRI-guidance with the current acoustic parameters are safe towards healthy brain tissue in a large in vivo model. These results further support growing interest in clinical translation of sonodynamic therapy for intracranial gliomas and other brain tumors.